Leadership hacks clever shortcuts to boost your impact and results - Stein, Scott 1968- (Findaway World, 2019)
A lifesaver for those drowning in the demands of leadershipLeadership Hacks is the business leader's guide to getting things done. Over the years, the leader's role has expanded to encompass more duties, more responsibility, and more accountability - yet we're still stuck with the same 24 hours in every day. The evolving business environment leaves many of us struggling to achieve against constantly shifting priorities, competitors, and deadlines, and we are forever expected to do more with less. Is it even possible to make a real impact? Yes! This book shows you how to sort through the madness and get back to getting results. Identify your major speed bumps, and let the action-focused discussion gives you practical workarounds that will streamline your day and help you make things happen. Covering hacks at personal, one-on-one, and team levels, this book is packed with tips, tricks, and advice that will help you eliminate the distractions and harness technology; communicate effectively, delegate clearly, and coach confidently; and make meetings and missions that matter for your team. You'll achieve greater results, open the channels of communication, and look like a rock star to those still struggling with the daily deluge.
Online resource; title from cover image (EBSCO, viewed March 21, 2019)
Keywords: Leadership; Management; Gestion; management; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Downloadable audio books; Audiobooks; Livres audio